2020
DOI: 10.1007/s40201-020-00488-7
|View full text |Cite
|
Sign up to set email alerts
|

Development and implementation of water safety plans for groundwater resources in the southernmost city of West Azerbaijan Province, Iran

Abstract: The transfer of water from the source to the consumption point is always associated with the possibility of contamination in any of its various components. To resolve this problem, the World Health Organization has considered a water safety plan. The purpose of this study is to implement water safety plan in the water supply system of Bukan city. This study was performed on Bukan’s water supply system in 2019–20 using a software to guarantee the quality of the water safety plan and the WHO and IWA guidelines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Therefore, with the obtained scores, it shows that the organization has paid more attention to the sources of supply and consumption point. Based on a study conducted in Spain and France, more consideration is paid to treatment plant and distribution networks in France and the source of water supply in Spain (23). In the water supply system of Talesh city, due to the heavy expenses of installation and maintenance, relatively brief regard is for to the distribution network, and these factors can affect the ultimate quality of water hand over to point of use in the near future.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, with the obtained scores, it shows that the organization has paid more attention to the sources of supply and consumption point. Based on a study conducted in Spain and France, more consideration is paid to treatment plant and distribution networks in France and the source of water supply in Spain (23). In the water supply system of Talesh city, due to the heavy expenses of installation and maintenance, relatively brief regard is for to the distribution network, and these factors can affect the ultimate quality of water hand over to point of use in the near future.…”
Section: Resultsmentioning
confidence: 99%
“…The scores of each department are 64%, 48%, 64%, and 154 points out of 352 total points, respectively, which shows the organization's more attention to the source of production and point of consumption. According to the study, the treatment plant and distribution network in France and the water supply source in Spain received the highest attention (27). Due to the high costs of installation and maintenance, less attention is paid to the distribution network of Talesh, and this affects the final quality of water delivered to consumers.…”
Section: Discussionmentioning
confidence: 99%
“…This study was suggested to identify the weaknesses and preventable points in the water supply system of Talesh, and highlight the need to change the existing attitude and the value of WSP in increasing the drinking water quality index. In addition, considering potential risks, appropriate solutions to reduce these risks in urban water supply systems will help (27).…”
Section: Introductionmentioning
confidence: 99%
“…Targets by 2030: Improve water quality by reducing pollution, eliminating waste disposal and minimizing the removal of chemicals and hazardous materials, halving the proportion of untreated wastewater, and substantially increasing recycling and safe reuse globally 2 The extraction or utilization of karst springs to meet various needs from year to year always increases, in line with the increasing population and growing needs of the community 3 . The everincreasing need for water causes humans to forget that the environment's carrying capacity has limits in meeting domestic and other needs such as industry, agriculture, and urban needs 4 Factors that affect the quantity and quality of karst springs in the future, including land cover conditions in rainwater catchment areas, land use activities in rainwater catchment areas, geomorphological and geological conditions, as well as consumption patterns or utilization of spring sources to meet population needs that are highly dependent on regional development and population growth 5. The quality of groundwater in a region is largely determined by natural processes (lithology, groundwater velocity, affix water quality, and interaction with other types of aquifers) and anthropogenic activities (agriculture, industry, urban development) and increased exploitation of water resources 6. Land use is one of the most critical factors determining water quality. However, very few studies have focused on the impacts of land use and land cover change on karst hydrogeochemical systems.…”
Section: Introductionmentioning
confidence: 99%